The Influence of Psychosocial Support, Health Communication, Information and Education (KIE), and Health Service Facilities on the Decision of Pregnant Mothers in Choosing Antenatal Care (ANC) and Delivery with Social-Media as a Moderating Variable at Pet - Gultom, Doddy Fernando Pausoan; Wahidi, Kemala Rita; Nofierni, Nofierni (Kontigensi : Jurnal Ilmiah Manajemen, 2025)
The decision of pregnant mothers to choose Antenatal Care (ANC) and delivery services is important because it affects hospital visits. The number of pregnant mothers visiting Petukangan General Hospital has shown a declining trend in 2023. Various health services for pregnant mothers have been provided, but they have not yet succeeded in increasing the number of visits. This research aims to analyze the role of Social Media Marketing as a moderating variable in the influence of psychosocial support, health communication, information and education (KIE), and health service facilities on the decision of pregnant mothers in choosing Antenatal Care (ANC) and delivery services at Petukangan General Hospital. Psychosocial support, which includes emotional and social support from family and healthcare providers, plays a crucial role in reducing anxiety and enhancing the comfort of pregnant mothers. Additionally, comprehensive health service facilities, such as specialist and subspecialist obstetric services, significantly influence the decisions of pregnant mothers. This study employs a causal quantitative research approach. The sample for this research consists of pregnant mothers residing in Jakarta who have utilized services at Petukangan Hospital at least twice, have plans to give birth, are aware of the hospital's Instagram social media, and are participants in the BPJS program. The total sample size is 220 pregnant mothers. The analysis technique used is Cross Sectional with the SEM-PLS measurement method. The study shows that psychosocial support and health service facilities have a significant influence on the decisions of pregnant mothers. Conversely, health communication, information, and education (KIE) do not have a significant effect. Social Media Marketing does not effectively moderate the relationship between these variables but has a direct and significant influence on the decisions of pregnant mothers through engaging and informative content. These results emphasize the importance of psychosocial support, quality service facilities, and effective digital marketing strategies to enhance the preferences of pregnant mothers for pregnancy services. Hospitals are recommended to strengthen their digital strategies to improve competitiveness in the healthcare market.